2006
DOI: 10.1074/jbc.m511690200
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic RAS Induces Accelerated Transition through G2/M and Promotes Defects in the G2 DNA Damage and Mitotic Spindle Checkpoints

Abstract: Activating mutations of RAS are prevalent in thyroid follicular neoplasms, which commonly have chromosomal losses and gains. In thyroid cells, acute expression of HRAS V12 increases the frequency of chromosomal abnormalities within one or two cell cycles, suggesting that RAS oncoproteins may interfere with cell cycle checkpoints required for maintenance of a stable genome. To explore this, PCCL3 thyroid cells with conditional expression of HRAS V12 or HRAS V12 effector mutants were presynchronized at the G 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
71
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 50 publications
5
71
1
1
Order By: Relevance
“…Further, MAPK are known to participate in the maintenance of G2/M arrest and they are required for exit from growth arrest and transition through mitosis. 26 In our previous study, we had found that Ras can induce CARF, and we show here that CARF inhibition reciprocally decreases Ras, leading to downregulation of the Ras-mediated MAPK pathway, possibly as a measure to halt the cell cycle. Nonetheless, using two independent assays including ERK-overexpressing and HT1080 cells, we found that the Ras-MAPK pathway is not essential for CARFinhibition-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, MAPK are known to participate in the maintenance of G2/M arrest and they are required for exit from growth arrest and transition through mitosis. 26 In our previous study, we had found that Ras can induce CARF, and we show here that CARF inhibition reciprocally decreases Ras, leading to downregulation of the Ras-mediated MAPK pathway, possibly as a measure to halt the cell cycle. Nonetheless, using two independent assays including ERK-overexpressing and HT1080 cells, we found that the Ras-MAPK pathway is not essential for CARFinhibition-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Genes regulated by miR-21 in thyroid cells are enriched in categories involved in cell cycle and DNA damage response, especially by looking selectively at downregulated genes. It has been reported that oncogenic Ras is able to induce chromosome instability and to accelerate G2/M transition (Abulaiti et al, 2006;Knauf et al, 2006), thus we hypotesize that miR-21 could contribute to the ability of Ras-transformed cells to overcome the G2 DNA damage checkpoint successfully. We plan to perform additional experiments to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the localisation of active ERK to the mitotic kinetochore is also suggested to regulate proteins involved in chromosome segregation during metaphase to anaphase transition (Shapiro et al, 1998;Zecevic et al, 1998). Furthermore, ERK is also described to associate with kinetochores during early prophase, but this association is not apparent at later stages of mitosis (Knauf et al, 2005). The fact that MAD2 functions through its localisation to kinetochore suggests that there may be a direct interaction between the MEK/ERK pathway and MAD2 in regulating mitosis.…”
Section: Discussionmentioning
confidence: 99%